Structural, dielectric, ferroelectric and impedance spectroscopic studies on Ba1-xSrxTiO3 (0.15 ≤ x ≥ 0:35) - Pandey S.; Parkash O.; Kumar D. (My University, 2025)
Compositions with x = 0.15, 0.20, 0.25, 0.30 and 0.35 were synthesized in the system Ba1-xSrxTiO3 using conventional solid state reaction method and characterized by X-Ray Diffraction (XRD), Raman spectroscopy and Scanning Electron Microscopy (SEM). Tetragonal phase was confirmed in all the samples using Rietveld refinement of the XRD patterns and observation of their Raman spectra. Dielectric and impedance measurements were carried out in the temperature range 300-723 K in the frequency range 1 Hz to 1 MHz. The samples exhibit diffuse phase transition (DPT). Equivalent circuit model involving combination of Constant Phase angle Elements (CPE) and resistances (R) was developed which represents the data well. Expressions for the values of resistances (R) were established in terms of composition and temperature empirically. P-E loops indicated normal ferroelectric behavior for all the samples. Dielectric constant was also measured in the frequency range 8-12 GHz in the X band of microwaves. © 2019 World Scientific Publishing Company.